GST in Indian Economy: It’s Benefits and Impact: The Impact of Goods and Services Tax on the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper is an analysis of what the impact of GST (Goods and Services Tax) is on Indian economy. Goods and services Tax is the considerable positive indirect tax reform which spreads all over the world and showing an increasing trend in more than 160 countries. In India also, it was implemented on 1st July, 2017 through the constitution Act, 2016. The first concept of GST came in 2000 and many debates were arising for the implementation of GST. But, India committed to introduce in July 2017.In GST, there is only one tax rate for both goods and a service to be levied by states and central governments and it is an indirect tax for the whole economy. GST replaces all the other indirect taxes like sales tax, excise, custom, VAT, service tax. It is a destination based tax i.e. where the goods and services are consumed. This paper throws an insight into to know about the advantages and impact on Indian economy